ICAR-CIRCOTâ€™s Training on Quality Evaluation of Cotton: An Analysis for 2014-17 - DESHMUKH, P. S.; BHARIMALLA, A. K.; PATIL, P. G.; ARUDE, V. G.; SUNDARAMOORTHY, C.; KAMBLE, D. U.; JADHAV, A. R.; RAM, CHANDRIKA (Cotton Research Journal, 2021)
A five day training programme on â€œQuality Evaluation of Cottonâ€ was conducted by ICAR-CIRCOT regularly for the benefit of various stakeholders on chargeable basis. After establishment as Technological Laboratory in 1923, training in CIRCOT started on stakeholders demand in 1932. Since then the training course has undergone significant changes in terms of duration and content. In India, cotton quality evaluation is accomplished largely by hand and eye, which is known to suffer from limitations of inconsistency, subjectivity and inaccuracy. Post- globalization, cotton sector all over the world had become quality conscious. Realizing the need for well-trained personnel, ICAR-CIRCOT conducted this training programme to evaluate quality of cotton on scientific and objective basis. Present paper analysed the trainee profiles, who attended training courses during 2014-17. Total 181 trainees attended training courses in 16 batches, out of which 97% were men, showing inequality in gender representation. Majority (98.34%) of trainees were from youth category (18-54 years of age), which is in conformity with the Youthful India profile. All trainees were educated, but 6.08% had education upto higher secondary. Training was conducted in graspable language, hence the lower education did not created problem to trainees. Among the trainees most of them belonged to general and other backward categories (87.85%), while 8.84 % and 3.31 % belonged to Schedules Castes (SCs) and Schedule Tribes (STs), respectively, showing less representation. The trainees attended training course were mostly employed and hence sponsored for training course with payment of Rs. 10000. Despite concession offered to weaker sections of society in consonance with the government guidelines, less number of trainees availed the benefit. Only 15 farmers attended training course, who had other profession or self-employment, apart from farming.